2022
DOI: 10.3390/ijms23137090
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives for Whole Genome Amplification in Forensic STR Analysis

Abstract: Modern PCR-based analytical techniques have reached sensitivity levels that allow for obtaining complete forensic DNA profiles from even tiny traces containing genomic DNA amounts as small as 125 pg. Yet these techniques have reached their limits when it comes to the analysis of traces such as fingerprints or single cells. One suggestion to overcome these limits has been the usage of whole genome amplification (WGA) methods. These methods aim at increasing the copy number of genomic DNA and by this means gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…The results of the above study showed that the quantity of DNA content in nails decreased in proportion to the length of immersion in seawater, this was due to abnormal exposures from the surrounding environment, resulting in irreversible damage to DNA hydrogen bonds. This condition damaged the purine-pyrimidine pair in DNA, where this purine-pyrimidine pair is the main component of the DNA structure 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the above study showed that the quantity of DNA content in nails decreased in proportion to the length of immersion in seawater, this was due to abnormal exposures from the surrounding environment, resulting in irreversible damage to DNA hydrogen bonds. This condition damaged the purine-pyrimidine pair in DNA, where this purine-pyrimidine pair is the main component of the DNA structure 15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the renewed interest in the method generated by these recent publications may result in further useful forensic applications. 117 In a recent non-empirical, theoretical study, Ge et al. using simulated mixtures demonstrate clusters of ≥7 haploid cells have ≥97.6% accuracy to the donor aSTR profile.…”
Section: Forensic Genetic Analysis Of Single Cellsmentioning
confidence: 99%
“…Similarly, in comparative genomic single cell hybridization (SCOMP), adaptors are attached to the enzymatically digested genome [28,29] (Figure 1D). With these true PCR-based approaches, it is possible to achieve complete amplification of the genome from different nucleic acid samples for applications in biomedical or forensic sciences, as described in other comprehensive reviews [30,31]. However, isothermal protocols are widely used for WGA and can achieve higher coverage breadth and lower false positive rates than PCR-based methods.…”
Section: Wga Protocols Based On Pcrmentioning
confidence: 99%